Analysis of commuting in Attica: The Attica commuting network - Stefanouli, Maria; Polyzos, Serafeim (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Many complex systems are organized in the form of a network embedded in space. Networks appear naturally in many fields of science, and are often inherently complex structures. Many complex networks show signs of modular structure, uncovered by community detection. Communities allow researchers to understand better the network by reducing its complexity. This study analyzes the inter-regional commuting systems of region Attica in Greece, employing approach of detection of complex network communities. In particular, in this paper, the administrative units of Attica are presented as a complex network, using as a criterion for the existence of a functional relationship and the identification of network communities (FUAs) the daily commuting. Network communities are identified through the modularity maximization method used to analyze complex networks. In parallel with this, through regression model application, the main factors affecting the out-commuting intensity of the municipalities of Attica are defined. The conclusions reached are of special interest for Greece as commuting in this country has not been studied yet extensively.